Molecular characterization of recent HoBi‐like pestivirus isolates from cattle showing mucosal disease‐like signs in India reveals emergence of a novel genetic lineage. Issue 2 (17th January 2021) - Kalaiyarasu, Semmannan; Mishra, Niranjan; Jayalakshmi, Konappan; Selvaraj, Palanisamy; Sudhakar, Shashi Bhushan; Jhade, Sandeep Kumar; Sood, Richa; Premalatha, Narayanasammi; Singh, Vijendra Pal
Abstract: Natural infections with HoBi‐like pestivirus (HoBiPeV) have been detected in cattle in South America, Europe and Asia with a range of clinical manifestations including fatal mucosal disease (MD). In India, although HoBiPeV in cattle has been reported, there is no information on currently circulating HoBiPeV strains and associated severe clinical disease. Between September 2018 and December 2019, suspected cases of bovine viral diarrhoea with severe disease in cattle were noticed in farmers' small holdings in Tamil Nadu State. To determine the extent of pestivirus infection, blood, serum, nasal or oral swab samples of 46 cattle from 18 villages were tested. Based on the real‐time RT‐PCR, antigen ELISA and nucleotide sequencing results, pestivirus was detected in nine cattle from eight villages in two districts and all pestiviruses were identified as HoBiPeV. All nine HoBiPeV‐infected cattle displayed clinical signs resembling MD and HoBiPeV isolates ( n  = 9) obtained were characterized at genetic and antigenic level. Phylogenetic analyses based on 5′‐untranslated regions (5′‐UTR), N pro and combined 5′‐UTR‐N pro gene sequences revealed that eight HoBiPeV isolates clustered into a clade, distinct from all reported HoBiPeV clades (a–d), whereas one belonged to HoBiPeV‐d clade, thus providing evidence of emergence of a novel HoBiPeV clade (e). This was also supported by HoBiPeV‐e clade‐specific amino acid substitutions in N pro and the antigenic reactivity patterns. The study demonstrates the existence and independent evolution of five HoBiPeV clades (four main clades) globally and surprisingly three exclusive to India. Also we confirm first HoBiPeV occurrence in southern India with predominant prevalence of HoBiPeV‐e strains. Besides demonstrating increased HoBiPeV genetic diversity, here we show association of HoBiPeV with severe clinical disease involving fatalities highlighting impact of HoBiPeV on cattle health. The emergence of a novel HoBiPeV lineage provides new insights on global HoBiPeV epidemiology and genetic diversity reiterating the need for continuous monitoring of HoBiPeV in India.